Electrodeposition of Gold Nanostructures at the Interface of a Pickering Emulsion. Issue 15 (17th May 2018) - Booth, Samuel G.; Alghamdi, Rafgah G.; Belić, Domagoj; Brust, Mathias
Abstract: The controlled electrodeposition of nanoparticles at the surface of an emulsion droplet offers enticing possibilities in regards to the formation of intricate structures or fine control over the locus or duration of nanoparticle growth. In this work we develop electrochemical control over the spontaneous reduction of aqueous phase Au(III) by heterogeneous electron transfer from decamethylferrocene present in an emulsion droplet – resulting in the growth of nanoparticles. As gold is a highly effective conduit for the passage of electrical current, even on the nanoscale, the deposition significantly enhances the current response for the single electron transfer of decamethylferrocene when acting as a redox indicator. The nanostructures formed at the surface of the emulsion droplets were imaged by cryo‐TEM, providing an insight into the types of structures that may form when stabilised by the interface alone, and how the structures are able to conduct electrons. Abstract : Midas touch : gold nanostructures are deposited at the interface of an emulsion droplet. The deposited gold exhibits fast electron transfer acting to extend the area of the working electrode. This is confirmed by the contrasting behaviour between organic emulsions and thin films.